Study of Criminal Hadiths and Qishash: Perspectives on Contemporary Islamic Legal Thought - Khaeruman, Badri (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This study explores the significance of Hadith in the formulation and application of Islamic criminal law, focusing particularly on the punishments of HudÃ»d and Qishas. This research delves into the historical and contemporary debates surrounding the acceptance and authenticity of the hadith as a legal source. This study analyzes legal provisions for crimes such as adultery, theft, and apostasy and investigates the principles of Qishas in cases of murder and physical harm. The findings highlight Hadith's critical role in providing detailed explanations and practical applications of Qur'anic principles, ensuring a comprehensive framework for justice and morality in Islamic societies. Specific punishments for crimes under HudÃ»d, such as stoning for adultery and amputation for theft, were examined as deterrents designed to maintain social order. This study also emphasises the balanced approach of the Qishas between justice and mercy, allowing for compensation or forgiveness in certain cases. Moreover, this research explores the adaptability of Islamic criminal law principles within contemporary legal frameworks, emphasising potential harmonisation with modern legal norms and addressing human rights considerations. This study underscores the relevance of the Hadith in contemporary legal and social contexts, offering insights into integrating traditional Islamic jurisprudence with modern legal practices.